Pengolahan Kerupuk Emping Melinjo Di BUMdes Desa Selubuk Kecamatan Air Napal - Sari, Serly Mayang (Jurnal Kewirausahaan dan Bisnis, 2023)
Emping melinjo crackers have a classy aroma and a delicious, crunchy taste. The process of processing melinjo fruit into emping melinjo crackers can be done in various ways. The first process is that old melinjo fruit are fried without oil with hot sand or rendang in a cauldron, some are also boiled. After this process, the hard rind of rnelinjo fruit is discarded. then the melinjo fruit is pounded or ground to form thin pieces. data collection is carried out by making direct observations on matters relating to the problem under study and referring to books, the internet and other sources that have to do with the preparation of the research The melinjo cracker makers usually carry out the process of forming thin chips on this melinjo traditionally which is stacked with stones on the foundation in stages. This study applied a processing system for emping melinjo crackers with a milling system. This grinding aims to facilitate the process of forming melinjo fruit into thin pieces. The expected results of this process indicate that the production capability of this tool is roughly estimated at around 15 melinjo pieces per minute.